PENYUSUNAN INDEKS KUALITAS KESEHATAN LINGKUNGAN (STUDI KASUS DI PELABUHAN TANJUNG EMAS SEMARANG) - Bintar Wahyu Ismail; Mursid Rahardjo; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2017)
Public Health around the harbor can be disturbed by various factors one of them due to high activity on the port that can cause environmental degradation of water, land and air. In addition carryover of disease vectors as well as the sanitary condition food management (TPM), which is in the port environment can also potentially cause or transmit disease. This research aimed to determine Environmental Quality Index at the Port of Tanjung Emas in Semarang. This type of research was a cross sectional research with descriptive analysis method with quantitative approach. Sample that been used in this research is sanitary hygiene quality sample of TPM and environmental parameters. The results of the analysis of the quality of hygiene and sanitation MDGs include both categories (Plj: 0.99), of 3 TPM examined contained 1 TPM are not eligible. Water quality including lightly polluted category (Plj: 3.24). The results of the examination of the parameters E. coli and lead (Pb) in water, and the pH, Pb and Total Suspended Solid (TSS) in the sea water obtained Pb parameter in clean water and sea water exceeding the threshold value (NAV). The air quality is good category (Plj: 0.64), the results of the examination of dust and Pb parameter, just dust in the air can be categorized as lightly polluted. Quality soil for examination Pb categorized as good (Plj: 0.03). The quality of noise includes both categories (Plj: 0.97). The quality of disease vectors including lightly polluted category (Plj: 2), the results of the examination of vector rats and flies, fly vector only were categorized as lightly polluted. The result of the calculation of the environmental quality index analysis showed that the Environmental Quality at the Port of Tanjung Emas Semarang still fall into the category of lightly polluted with total index score of 1,474.